The Use of Modular Object-Oriented Dynamic Learning Environment (MOODLE) Learning Management System (LMS) in Learning Evaluation at SMK Brantas Karangkates - Al Habiib, Hiya Latief; Rofiq, Muhammad (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study aims to examine the implementation of technology in educational assessments, specifically using the Learning Management System (LMS) Moodle at SMK Brantas Karangkates. Traditional paper-based tests limit multimedia integration and efficient scoring, whereas online exams offer a more effective and streamlined alternative for learning evaluations. Method: The research focuses on Moodle’s implementation process, detailing steps like preparing questions, setting up quiz features, conducting exams, and managing automated scoring. Observational data and school records were used to analyze Moodle's application. Practical Applications: Using LMS Moodle, with its multimedia and automated grading capabilities, enhances exam efficiency, accessibility, and result management. This practical approach supports schools in modernizing their assessment processes. Conclusion: SMK Brantas Karangkates has effectively used Moodle for online exams over the past five years, showing significant improvements in assessment efficiency. This study illustrates how e-learning platforms like Moodle can support schools in adapting to technological changes in education.